2022
DOI: 10.1038/s41598-022-05708-8
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of the inflammatory response in mid colon of complement component 3 knockout mice

Abstract: To determine whether complement component 3 (C3) deficiency affects its receptor downstream-mediated inflammatory response, the current study was undertaken to measure alterations in the inducible nitric oxide synthase (iNOS)‑mediated cyclooxygenase‑2 (COX‑2) induction pathway, inflammasome pathway, nuclear factor-κB (NF-κB) activation, and inflammatory cytokine expressions in the mid colon of C3 knockout (KO) mice. Significant enhancement was observed in expressions of key components of the iNOS‑mediated COX‑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Colon cancer cells undergo oxidative damage-arbitrated apoptosis as a result of oxidative stress. Overgeneration or elimination of ROS causes severe damage to the intracellular molecules (Choi et al, 2022). It has been observed that plant-based chemo-preventive agents elevate the generation of ROS and disrupt the homeostasis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer cells undergo oxidative damage-arbitrated apoptosis as a result of oxidative stress. Overgeneration or elimination of ROS causes severe damage to the intracellular molecules (Choi et al, 2022). It has been observed that plant-based chemo-preventive agents elevate the generation of ROS and disrupt the homeostasis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the effect of C3 deficiency on the colonic inflammatory response revealed that the absence of C3 is associated with the upregulation of proinflammatory cytokines and the downregulation of tight junction channels due to an increase in inducible nitric oxide synthase (iNOS)-mediated cyclooxygenase-2 (COX-2) production. 49 While these data suggest a potential protective role of C3 in both UC patients and animal models of colitis, other studies suggest that C3 may play a pathogenic role. For example, Elisabeth et al found that C3aR contributes to the progression of DSS-induced colitis in BALB/c mice.…”
Section: Complement Regulationmentioning
confidence: 97%
“…These findings suggest that both extracellular and intracellular C3 fragments can protect the integrity of the intestinal mucosa by promoting intestinal epithelial cells (IECs) proliferation; however, further study is required to assess this. A recent study of the effect of C3 deficiency on the colonic inflammatory response revealed that the absence of C3 is associated with the upregulation of proinflammatory cytokines and the downregulation of tight junction channels due to an increase in inducible nitric oxide synthase (iNOS)‐mediated cyclooxygenase‐2 (COX‐2) production 49 . While these data suggest a potential protective role of C3 in both UC patients and animal models of colitis, other studies suggest that C3 may play a pathogenic role.…”
Section: Role Of the Complement System In Ucmentioning
confidence: 99%
“…However, animal models and complement antagonists which were originally created to investigate innate immunity are also providing insights into other cellular processes; for instance, C3 −/− mice are protected against bone loss in an ovariectomized osteoporosis model, 156 injury-induced neurogenesis, 157,158 pregnancy-associated complications, 159 and inflammatory bowel disease. 160 It is beyond the scope of this review to discuss all these scientific discoveries in detail, so we will concentrate on a few key areas: the controversy of "intracellular complement," metabolism and metabolic disorders and age-related macular degeneration (AMD). suggesting that the original T cell data may be applicable to all cell types.…”
Section: The Multifarious Ap/al: Broadening the Scope Of Complement R...mentioning
confidence: 99%